Nonlinear Rheology: a New Framework for the Characterization of Skin Pressure Sensitive Adhesives - Kuzgun, Sinan (My University, 2017)
The main goal for this degree project is to investigate the significance of nonlinear viscoelasticity while characterizing skin pressure sensitive adhesives. This evaluation was investigated via oscillatory shear tests, Fourier-trasform rheology, Lissajous – Bowditch diagrams and their quantification and also performing oscillatory frequency sweeps in order to compare the nonlinear viscoelastic methods with the conventional linear viscoelastic methods. Five individual polymer materials and two end products provided by Coloplast were tested during thesis work. Individual polymer materials were two cohesive agents (one of them crosslinked), one softener, one softener/tackifier and one plasticizer. One of the end products is the commercially sold skin pressure sensitive adhesive (which will be referred as Colo1) and the other one is the recently developed skin pressure sensitive adhesive (which will be referred as Colo2). Main tests performed on all materials were strain sweep and frequency sweep. Sample preparation, testing parameters and methods were optimized. Base temperature selected was 33C due to the expected skin temperature but due to the nature of certain materials, some tests were performed at elevated temperatures of up to 200C. Experiments have brought out the importance of higher harmonics in the Fourier spectra and quantification of Lissajous-Bowditch diagrams in terms of sensitivity and novel quantification of skin pressure sensitive adhesives. Results brought that a framework of novel characterization methods using nonlinear viscoelasticity can be developed in addition to the conventional linear viscoelastic measurements. Even though this degree project is only a beginning, the potential of nonlinear viscoelastic measurements brought by this study is worth investigating for future references.
Keywords: Textil-, gummi- och polymermaterial; Biomaterialvetenskap; Livsvetenskaper; Materialvetenskap; Textile, Rubber and Polymeric Materials; Biomaterials Science; Life Science; Materials Science